Examining the external training load of an English Premier League football team with special reference to acceleration - Akenhead, R.; Harley, J.; Tweddle, S. (The Journal of Strength and Conditioning Research, 2016)
Practitioners and coaches often use external training load variables such as distance run and the number of high-speed running (HSR) activities to quantify football training. However, an important component of the external load may be overlooked when acceleration activities are not considered. The aim of this study was to describe the within-microcycle distribution of external load, including acceleration, during in-season 1-game weeks in an elite football team. Global Positioning System technology was used to collect time-motion data from 12 representative 7-day microcycles across a competitive season (48 training days, 295 data sets). Training time, total distance (TD), high-speed running (HSR) distance (>5.8 m/s), sprint running distance (>6.7 m/s) and acceleration variables were recorded during each training session. Data were analysed for interday and interposition differences using mixed linear modeling. The distribution of external load was characterized by the second training day of the microcycle (5 days prematch) exhibiting the highest values for all variables of training load, with the fourth day (1 day prematch) exhibiting the lowest values. Central midfield players covered ~8-16% greater TD than other positions excluding wide midfielders (p = 0.03, d = 0.2-0.4) and covered ~17% greater distance accelerating 1-2 m·s-2 than central defenders (p = 0.03, d = 0.7). When expressed relative to training duration and TD, the magnitude of interday and interposition differences were markedly reduced (p = 0.03, d = 0.2-0.3). When managing the distribution of training load, practitioners should be aware of the intensity of training sessions and consider the density of external load within sessions.